2020
DOI: 10.3390/scipharm88020023
|View full text |Cite
|
Sign up to set email alerts
|

Michelia Essential Oil Inhalation Increases Fast Alpha Wave Activity

Abstract: Essential oils are volatile fragrance liquids extracted from plants, and their compound annual growth rate is expected to expand to 8.6% from 2019 to 2025, according to Grand View Research. Essential oils have several domains of application, such as in the food and beverage industry, in cosmetics, as well as for medicinal use. In this study, Michelia alba essential oil was extracted from leaves and was rich in linalool components as found in lavender and jasmine oil. The effects of inhaling michelia oil on hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Garlic oil demonstrated the lowest threshold property compared with Litsea cubeba and Curcuma longa oils. The increase in alpha wave power can be observed in several essential oil, such as white champaka, eucalyptus, lavender, and Zizyphus jujuba oils [ 14 , 26 , 27 , 28 ]. This alteration is related to psychometric responses, a relaxing effect, an increase in attention and relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Garlic oil demonstrated the lowest threshold property compared with Litsea cubeba and Curcuma longa oils. The increase in alpha wave power can be observed in several essential oil, such as white champaka, eucalyptus, lavender, and Zizyphus jujuba oils [ 14 , 26 , 27 , 28 ]. This alteration is related to psychometric responses, a relaxing effect, an increase in attention and relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data were shown in Table 3 . The method was slighted modified from Kim et al, 2018, and Koomhin et al, 2020 [ 14 , 32 ]. To replicate odor or fragrance application in the real-life situation, the odor was attached near volunteer nose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects’ baseline characteristics are shown in Table 4 ; Table 5 . The method was slighty modified from Koomhin et al 2020 [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the alpha component placed at each participant's occipital lobe showed significant increases during the inhalation of the LG sample of common rush. Previous studies have shown that the alpha component can increase when participants perceive scents produced by natural plants [32]. One of the compounds, benzaldehyde, was used as a chemical flavoring, particularly to mimic "cool mint".…”
Section: Discussionmentioning
confidence: 99%